Конституційно-правові засади організації місцевої влади Української РСР - Іванова, Т.М. (Держава і право, 2011)
Розкриваються
особливості
організації
місцевої
влади
за доби
Української
РСР,
аналізується законодавство
що регулювало
питання
здійснення
влади
на місцевому
рівні. Раскрываются
особенности
организации
местной
во время
развития
Украинской
ССР, анализируется
законодательство,
которое
регулировало
вопрос
осуществления
власти
на местном
уровне. The article addresses the specifics of legislative strengthening of local authorities for the
day of the Ukrainian SSR, the problem of practice implementation at the local level and on
the basis of historical experience made proposals on improvement of legislation and the
Organization of local government in modern Ukraine.